Effect of engagement and collaborative learning on satisfaction through the use of social media on Malaysian higher education - Al-Rahmi, Waleed Mugahed (Maxwell Science Publications, 2015)
As social networks continue to proliferate, the question arises as to how to attract students and researchers to different online sites. In this regard, the present study focused on the interactivity of social networks and their role in satisfying students. Accordingly, this study proposed a model comprising of factors that assist in answering the study questions. A developed questionnaire was then distributed to 132 students and users' of social media websites that obtains relevant information regarding technology acceptance, interactivity and satisfaction of students. The findings suggested that both Technology Acceptance Model (TAM) related factors as well as interactivity affect the satisfaction and academic performance of students.